The Effect of Learning Media Use on Conceptual Understanding Ability in Students with Low Mathematical Ability - Salsabila Intan; Tina Yunarti; Santy Setiawati (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2026)
Abstract: Conceptual understanding is a fundamental skill essential for students in learning mathematics. This study aims to analyze the effect of instructional media on the conceptual understanding of students with low mathematical ability. The subject matter focused on linear equations and inequalities in one variable, utilizing instructional media such as comic-based worksheets, snakes and ladders games, buffalo paper, domino cards, and word puzzles. The population consisted of 233 seventh-grade students at a public junior high school in Bandar Lampung during the first semester of the 2024/2025 academic year, with a sample of 29 students selected through purposive sampling. The research employed a quasi-experimental method with a one-group pretest-posttest design, using the Mid-Semester Examination scores as the pretest. The Wilcoxon test results indicated sig. (2-tailed) = 0.00 < 0.05, showing the use of instructional media has a positive effect on the conceptual understanding of students with low mathematical ability. Abstrak: Pemahaman konsep merupakan keterampilan dasar yang penting bagi siswa dalam mempelajari matematika. Penelitian ini bertujuan menganalisis pengaruh penggunaan media pembelajaran terhadap pemahaman konsep siswa dengan kemampuan matematika rendah. Materi yang dikaji adalah persamaan dan pertidaksamaan linear satu variabel, dengan media berupa LKPD komik matematika, permainan ular tangga, kertas buffalo, kartu domino, dan puzzle kata. Populasi penelitian terdiri atas 233 siswa kelas VII di salah satu SMP Negeri Bandar Lampung pada semester gasal 2024/2025, dengan sampel 29 siswa yang dipilih melalui purposive sampling. Penelitian menggunakan metode quasi eksperimen dengan desain one group pretest-posttest, dengan nilai pretest diambil dari Ujian Tengah Semester. Hasil uji Wilcoxon menunjukkan sig.(2-tailed) = 0,00 < 0,05, yang berarti penggunaan media pembelajaran berpengaruh positif terhadap pemahaman konsep siswa berkemampuan matematika rendah.